The Implementation of Parties Autonomy and Authority of Bani Region of Business Disputes Resolution - Sidik, Jafar (BANI Arbitration and Law Journal, 2024)
Badan Arbitrase Nasional Indonesia so called BANI Arbitration Center (“BAC”) is an independent institution that provides services in settling disputes outside the state court. BANI is domiciled in Jakarta and there are BANI Region located in various big cities in Indonesia: Bandung, Surabaya, Medan, Denpasar, Palembang, Pontianak, and Jambi, acting autonomously and independently in upholding law and justice. The parties still have disagreements on where to take themselves if there is a dispute between them. Dispute settlement through BANI has become the choice of business actors to resolve their trade disputes. In addition to the characteristics of being fast, efficient, and thorough, arbitration adheres to the principle of a win-win solution and is straight forward because there are no appeals and cassation institutions. The arbitration fee is also more measurable because the process is faster. Another advantage of arbitration is that its decisions are immediately (final) and binding, apart from its confidential nature, in which the trial process and arbitration award are not published. The object of the study is the settlement of business dispute through BANI Region. The purpose of this writing is to analyze and describe (a) how does the implementation of parties authonomy in arbitration; (b) can the parties choose the forum of arbitration through BANI Region? (c) Has BANI Region have the authority or competency to examine and decide business disputes? (d) to what extent is the role of BANI Region in law enforcement in Indonesia? This paper uses a normative juridical approach with a qualitative analysis method on RI Law No. 30 Year 1999 concerning Arbitration and Alternative Dispute Resolution and the 2022 BANI Rules and Procedures. The conclusion are that the disputing parties (a) They implemented parties authonomy in arbitration; namely befor, during and after dispute arises till the implement of arbitral award; (b) They can choose forum for dispute settlement through BANI Region; (c) BANI Region have the authority to examine and decide trade disputes; (d) BANI Region have a strategic role in law enforcement in Indonesia.